The Value of Preregistration for Open and Credible Science: An Initiative from the Journal of Experimental Political Science. Issue 3 (2018) - Arceneaux, Kevin; Wilson, Rick; Boudreau, Cheryl; Bush, Sarah; Jerit, Jennifer; Rubenson, Daniel; Sinclair, Betsy; Settle, Jaime; Woon, Jonathan; Zechmeister, Elizabeth
Abstract : In the interest of promoting open and reproducible science, the Journal of Experimental Political Science editorial team will pilot the pre-acceptance of preregistered reports. We note that the launch of this new submission option is a complement to, and does not replace, the option to submit other types of manuscripts. JEPS remains open to receiving and reviewing high quality manuscripts regardless of whether they are based on preregistered studies.